2016
DOI: 10.4236/ijg.2016.71003
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Chemistry of REE-Rich Apatite and Sulfur-Rich Monazite from the Mushgai Khudag, Alkaline Volcanic-Plutonic Complex, South Mongolia

Abstract: The Mushgai khudag volcanic-plutonic complex consists of four REE mineralization zones: carbonatite zone, apatite zone, magnetite zone, and monazite zone. REE mineralization occurs within peripheries of alkaline magmatic rocks which consist of porphyritic syenite, microsyenite and quartz syenites. Three types of LREE-rich apatite can be found in the carbonatite, apatite, and monazite zones. Crystal-1 type of apatite exists as hexagonal prismatic shape and is mostly found in the apatite zone, and in syenite. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…In the Catalao I carbonatite complex, weathered monazite displayed a less steep REE pattern (i.e., lower La/Nd ratio) when compared to those within carbonatite [28]. The detailed chemical compositions of monazite within carbonatite related environments can be found in Supplementary Materials Table S2 [ [11][12][13][14][16][17][18]20,23,24,29,30,34,35,[37][38][39][40][41][42][43].…”
Section: Ree Compositionsmentioning
confidence: 99%
“…In the Catalao I carbonatite complex, weathered monazite displayed a less steep REE pattern (i.e., lower La/Nd ratio) when compared to those within carbonatite [28]. The detailed chemical compositions of monazite within carbonatite related environments can be found in Supplementary Materials Table S2 [ [11][12][13][14][16][17][18]20,23,24,29,30,34,35,[37][38][39][40][41][42][43].…”
Section: Ree Compositionsmentioning
confidence: 99%
“…To accommodate this imbalance, Chakhmouradian and Mitchell (1999) suggested the presence of an auxiliary substitution mechanism:
Fig. 7.Composition of monazite-(Ce) from Eureka compared with data compiled from other carbonatite complexes (circles; Kukharenko et al ., 1961; Cressey et al ., 1999; Bulakh et al ., 2000; Doroshkevich et al ., 2001; Wall, 2004; Lazareva et al , 2015; Enkhbayar et al ., 2016; Prokopyev et al , 2017; Nikolenko et al , 2018), the Internatsional'naya kimberlite (Chakhmouradian and Mitchell, 1999), and other published occurrences (squares) with SO 3 >1% (Ondrejka et al , 2007; Pršek et al , 2010; Krenn et al ., 2011; Ondrejka et al ., 2016).
…”
Section: Discussionmentioning
confidence: 99%
“…A compilation of monazite-(Ce) compositions from different carbonatites was presented by Chen et al (2017). The majority of these data have <1% SO 3 , in addition, published occurrences with monazite-(Ce) containing >1% SO 3 are limited to Nkombwa, Zambia (Wall, 2004); Vuoriyarvi and Seligdar, Russia (Kukharenko et al , 1961; Bulakh, 2000; Prokopyev et al , 2017); and Mushgai Khudag, Mongolia (Enkhbayar et al , 2016; Nikolenko et al , 2018). In all of these occurrences, monazite-(Ce) forms at a late stage in the crystallisation history of the carbonatites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed mineralogical characterization of the ore was conducted by Enkhbayar et al [14], who found that REEs were mostly associated with fluorapatite and hydroxyapatite. As shown in Figure 2, the apatite grains have hexagonal structures with a layered arrangement of outer crystals grown upon an inner layer of crystals.…”
Section: Mineralogical Characteristics Of the Samplementioning
confidence: 99%